Identifikasi Fenotip Generasi Induk (G0) dan Generasi Pertama (G1) Pola Perkawinan Assortative terhadap Hasil Produksi Pada Ayam Kokok Balenggek - Chania Chania; Rusfidra Rusfidra; Subekti Subekti (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
AKB is a native chicken from West Sumatra. The Minang people reportedly call it Balenggek chicken which has a cascading rhythmic crowing sound. AKB comes from crosses of the Red Junglefowl (Gallus gallus) with local chickens. AKB is a source of wealth for local livestock in Indonesia that needs to be protected and preserved . This research consisted of two stages. The first stage of the research aimed to identify the qualitative and quantitative characteristics and the second stage of the research aimed to determine the first generation phenotype (G1) resulting from the Assortative mating pattern on production in IMR. This second stage of research used 8 male AKBs. and 48 females that are sexually mature. Based on the results of the identification of qualitative and quantitative characteristics research, it shows that the qualitative characteristics of male AKB based on feather pattern are dominated by columbian type, striated feather pattern, silver and gold flickering feathers, yellow/white shank color, single type comb shape, yellow/white beak color . Based on the pattern of feathers, the female AKB is dominated by the columbian type, striated feather pattern, golden feather flickering, yellow/white shank color, single comb type and yellow/white beak color. The coefficient of diversity of high quantitative traits in male AKB is neck diameter (22.22%), comb height (18.45%) and for females is comb height (29.60%) and body weight (18.77%) . Based on the results of the second phase of the study, the average weight of DOC IMR was 24.31 grams. Mating based on the similarity of fur color, produces offspring with the same fur color as their parents. P1, P2, P3, P4 relatively the same growth pattern.